Implementasi Kebijakan Smart Desa di Desa Cisalak Kabupaten Subang - Fadli Alfikri; M. Reihan Faujanegara; Audra Farrell Holliano; Ivan Darmawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This study aims to examine the Implementation of the Smart Village Policy in Cisalak Village, Subang Regency. This is based on the low level of Smart Village achievements shown through the smart village web in Cisalak Village, Subang Regency. This research uses a qualitative approach with a descriptive study through interviews and literature studies. While data management by analyzing the results of interviews. And located in Cisalak Village, Subang Regency. The results of the research show that the implementation of the Smart Village policy in Cisalak Village has not run optimally. This is because there are still many people in Cisalak Village who do not understand the function of this smart village policy as well as the limited ability to use today's technology so that this policy does not work properly and optimally.